Pharmacological Targeting of GLUT1 to Control Autoreactive T Cell Responses - Di Dedda, Carla (Int J Mol Sci, 2019)
An increasing body of evidence indicates that bio-energetic metabolism of T cells can be manipulated to control T cell responses. This potentially finds a field of application in the control of the T cell responses in autoimmune diseases, including in type 1 diabetes (T1D). Of the possible metabolic targets, Glut1 gained considerable interest because of its pivotal role in glucose uptake to fuel glycolysis in activated T cells, and the recent development of a novel class of small molecules that act as selective inhibitor of Glut1. We believe we can foresee a possible application of pharmacological Glut1 blockade approach to control autoreactive T cells that destroy insulin producing beta cells. However, Glut1 is expressed in a broad range of cells in the body and off-target and side effect are possible complications. Moreover, the duration of the treatment and the age of patients are critical aspects that need to be addressed to reduce toxicity. In this paper, we will review recent literature to determine whether it is possible to design a pharmacological Glut1 blocking strategy and how to apply this to autoimmunity in T1D.